2012
DOI: 10.5489/cuaj.85
|View full text |Cite
|
Sign up to set email alerts
|

Two primary seminomas in a patient with polyorchidism

Abstract: We report the clinical, radiographic and pathological findings of polyorchidismand a right-sided abdominal seminoma found in a 28-year-old man who presentedwith cryptorchidism in childhood and who later underwent an orchiectomyfor a left-sided seminoma. Pathological analysis of the abdominal tumour revealed the existence of a classic seminoma bordered by a rim of non-tumour tissue and remnants of epididymis. We propose that patients who present with cryptorchidism be assessed for polyorchidism as this might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Due to the relatively low incidence of cancers associated with SNT, it is not easy to assess which histological types are the most common. For the cases included in our analysis, histopathological examinations revealed seminoma and intratubular germ cell neoplasia (IGCN) [ 24 , 59 ]. Bergholz et al [ 3 ] also reported choriocarcinoma, teratoma, and embryonal carcinoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the relatively low incidence of cancers associated with SNT, it is not easy to assess which histological types are the most common. For the cases included in our analysis, histopathological examinations revealed seminoma and intratubular germ cell neoplasia (IGCN) [ 24 , 59 ]. Bergholz et al [ 3 ] also reported choriocarcinoma, teratoma, and embryonal carcinoma cases.…”
Section: Discussionmentioning
confidence: 99%
“…3 The occurrence of malignant tumors like seminoma or germ cell tumors in supernumerary testis has been described and explains the potential need for followup with ultrasonographic surveillance of these patients. 8 The ultrasonographic hallmark of polyorchidism is the identification of a scrotal mass, which appears identical to the ipsilateral testis on every ultrasonographic technique performed, including echogenicity pattern on B-mode. 1,6,9 This mass may be found attached to the ipsilateral testis or separated and located superiorly or inferiorly.…”
Section: Discussionmentioning
confidence: 99%
“…3 The occurrence of malignant tumors like seminoma or germ cell tumors in supernumerary testis has been described and explains the potential need for follow-up with ultrasonographic surveillance of these patients. 8…”
Section: Discussionmentioning
confidence: 99%
“…Tumors reported in patients with polyorchidism include intrascrotal rhabdomyosarcoma, testicular teratoma, seminoma, and choriocarcinoma [136][137][138]. Orchidectomy has been traditionally indicated in all atrophic testes and those located out of the scrotum [139].…”
Section: Low-transversal Division Of the Genital Ridgementioning
confidence: 99%